2011
DOI: 10.1111/j.1751-7176.2010.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Effects of Naproxcinod in Hypertensive Patients

Abstract: The blood pressure (BP) effects of naproxcinod and naproxen were assessed in an 8‐week, double‐blind, crossover study in 131 hypertensive patients aged 50 to 74 years. Patients received naproxcinod 750 mg twice daily or naproxen 500 mg twice daily, then the alternate treatment, each for 14 days, with placebo run‐in/washout before each active treatment period and 24‐hour ambulatory BP monitoring conducted before and after each active treatment period. Mean change from baseline in average 24‐hour systolic BP (SB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Contrastingly, naproxcinod completed phase III clinical trials. Taken together, the results showed its efficacy in treating knee and hip osteoarthritis without increasing the systolic blood pressure of normo or hypertensive patients . Although some pilot trials also indicated that naproxcinod exhibited better GI tolerability, this NO‐releasing derivative of naproxen failed to significantly reduce the primary endpoint of 6 weeks endoscopic gastroduodenal ulcer incidence in a double blind study in patients with hip or knee osteoarthritis .…”
Section: Association Of Nsaids With Protective Mediatorsmentioning
confidence: 94%
“…Contrastingly, naproxcinod completed phase III clinical trials. Taken together, the results showed its efficacy in treating knee and hip osteoarthritis without increasing the systolic blood pressure of normo or hypertensive patients . Although some pilot trials also indicated that naproxcinod exhibited better GI tolerability, this NO‐releasing derivative of naproxen failed to significantly reduce the primary endpoint of 6 weeks endoscopic gastroduodenal ulcer incidence in a double blind study in patients with hip or knee osteoarthritis .…”
Section: Association Of Nsaids With Protective Mediatorsmentioning
confidence: 94%
“…In these studies gastrointestinal side effects and hypertension, commonly seen with NSAIDs, were kept to a minimum through the release of nitric oxide [130, 131]. …”
Section: Scientific Rationale and Competitive Environmentmentioning
confidence: 99%
“…The addition of the NO-donating moiety was aimed at reducing common adverse effects of chronic NSAID use, such as gastrointestinal damage and increased blood pressure. Indeed, naproxcinod was shown in several clinical trials to be effective in relieving the signs and symptoms of OA compared to placebo [ 27 , 34 36 ], but with a lower incidence of hypertension compared to NSAIDs [ 37 , 38 ]. Moreover, it has been demonstrated that the effects of naproxcinod ascribed to NO such as the control of blood pressure (BP) persist over time [ 38 ] up to 13 weeks, suggesting that the compound does not lead to development of nitrate tolerance with the chronic use.…”
Section: Discussionmentioning
confidence: 99%